Smart city and urban logistics - research trends and challenges: systematic literature review - Chocholáč, Jan; Kučera, Tomáš; Sommerauerová, Dana; Hruška, Roman; Machalík, Stanislav; Křupka, Jiří; Hyršlová, Jaroslava (My University, 2023)
The paper presents a systematic quantitative and qualitative literature review and classification of the last decades resources for a comprehensive and coherent view of smart city and urban logistics research trends and challenges. The review fully respects a six-step systematic literature review guideline and covers ninety-nine peer-reviewed articles from Web of Science Core Collection database. The review focuses on the following aspects: a perspective state-of-art journal, methods, content, keywords, references, and citations. The relevant articles for subsequent detailed analysis were identified between 2014 and 2020. The analysis has brought the following result: more than one third of the articles was published in 2020, the most articles were published in the Sustainability, and the modelling method was prevailed.
Chytrá města a urbánní logistika - výzkumné trendy a výzvy: systematická literární rešerše
Keywords: smart city; logistics; technology; mobility; vehicle routing problem; city logistics; chytré město; logistika; technologie; mobilita; problém okružních jízd vozidel; městská logistika